2018
DOI: 10.1002/jcb.27794
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates spinal cord injury by suppressing the activation of inflammasomes in rats

Abstract: Background The activation of inflammasomes plays an important role in the pathogenesis of spinal cord injury (SCI). In addition, the administration of melatonin (MT) has been shown to suppress the activation of inflammasomes. In this study, we aimed to investigate the molecular mechanisms underlying the therapeutic effect of MT in the treatment of SCI. Methods Basso‐Beattie‐Bresnahan (BBB) locomotion scaling was conducted to evaluate the therapeutic effect of MT on post‐SCI locomotion recovery. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
(144 reference statements)
0
19
1
Order By: Relevance
“…Recent studies on mouse brain injury and major depressive disorder models showed that the anti-inflammatory effect of melatonin was partially attributed to the suppression of NLRP3 inflammasome activity, where melatonin reduced the expression of NLRP3 inflammasome components and the protein levels of IL-1β. [16][17][18] However, the inhibitory effect of melatonin on NLRP3 inflammasome activation in PD per se has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on mouse brain injury and major depressive disorder models showed that the anti-inflammatory effect of melatonin was partially attributed to the suppression of NLRP3 inflammasome activity, where melatonin reduced the expression of NLRP3 inflammasome components and the protein levels of IL-1β. [16][17][18] However, the inhibitory effect of melatonin on NLRP3 inflammasome activation in PD per se has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] It is also considered that melatonin can provide protection against SCI by decreasing SCI-induced oxidative injury in rat kidney, 20 attenuating calpain upregulation, axonal damage and neuronal death, 21 as well as reducing SCI-induced functional and biochemical changes in rat urinary bladder. 22 Melatonin can inuence several molecular signaling pathways, such as PI3K/AKT/mTOR signaling, 23 Wint/b-catenin signaling 24 and the activation of inammasome, 25 during this process. However, the relationship between melatonin and IGFBP3 in the SCI development is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…inflammation is a crucial factor in secondary damage following Sci, and anti-inflammatory therapy contributes to recovery from Sci (34,35). nrf2 is a factor that regulates the transcription of cytoprotective genes, including Ho-1 and NQO1, thereby playing a pivotal role in anti-inflammatory response (36).…”
Section: Discussionmentioning
confidence: 99%